New insights into diet breadth of polyphagous and oligophagous aphids on two Arabidopsis ecotypes. (19th February 2018) - Wattier, Christopher; Turbant, Amélie; Sargos‐Vallade, Lisa; Pelloux, Jérôme; Rustérucci, Christine; Cherqui, Anas
Abstract: We investigated whether plant ecotype might affect aphid performance and behavior. The probing behaviors of the polyphagous aphid Myzus persicae and the oligophagous aphid Brevicoryne brassicae on two ecotypes of Arabidopsis thaliana, WS and Col‐0 were recorded using the direct current electrical penetration graph method (DC‐EPG). Myzus persicae displayed a significant preference for the WS ecotype but was not greatly disturbed on Col‐0, while B. brassicae discriminated between the two A. thaliana ecotypes, feeding less on WS than on Col‐0. A Principal Component Analysis of aphid probing behavior data recorded on Col‐0 and WS ecotypes showed that the one of M. persicae was positively correlated with the phloem ingestion phases while the one of B. brassicae was more related to nonfeeding phase. The survival of the aphid species was followed during early larval stages on the two ecotypes and a significantly higher mortality was observed of B. brassicae neonates compared to M. persicae, both reared on WS. Moreover, transcriptomic analysis of noninfested plant leaves from both ecotypes was monitored and underlined constitutive differences between Col‐0 and WS gene expression that might explain the different aphid behaviors. Among a unigene set comprising 39 042 sequences for A. thaliana, 6% were differently expressed affecting, for example, the secondary metabolites and cell wall pathways: two third upregulated in WS and one third upregulated in Col‐0. Thus, the "ecotype" variable should be taken into account when setting up a plant–insect experimental research.